2018
DOI: 10.3390/chemosensors6020017
|View full text |Cite
|
Sign up to set email alerts
|

A Rationally Designed, Spiropyran-Based Chemosensor for Magnesium

Abstract: Magnesium ions (Mg 2+ ) play an important role in mammalian cell function; however, relatively little is known about the mechanisms of Mg 2+ regulation in disease states. An advance in this field would come from the development of selective, reversible fluorescent chemosensors, capable of repeated measurements. To this end, the rational design and fluorescence-based photophysical characterisation of two spiropyran-based chemosensors for Mg 2+ are presented. The most promising analogue, chemosensor 1, exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This result indicated that cytosolic Mg 2+ played a vital role in governing intracellular formation of 2D-CB [6], consistent with the fact that 1) the concentration of cytosolic Mg 2+ (0.6-0.8 mm) exceeded that of Ca 2+ (2-3 µm) by approximately 300-fold, [27] and 2) MC displayed a 3-fold higher binding affinity for Mg 2+ (K a = 1.6 × 10 5 m −1 ) over Ca 2+ (K a = 0.5 × 10 5 m −1 ). [28] Since the resultant 2D materials in Figure 4c 1 -c 3 were micrometer-sized (Figure 5a,b), we believed they were too large to be endocytosed from outside the cell. This conclusion was confirmed by flow cytometric analysis of cells incubated with 2D-CB [6] extracted from their "mother" cells.…”
Section: Resultsmentioning
confidence: 98%
“…This result indicated that cytosolic Mg 2+ played a vital role in governing intracellular formation of 2D-CB [6], consistent with the fact that 1) the concentration of cytosolic Mg 2+ (0.6-0.8 mm) exceeded that of Ca 2+ (2-3 µm) by approximately 300-fold, [27] and 2) MC displayed a 3-fold higher binding affinity for Mg 2+ (K a = 1.6 × 10 5 m −1 ) over Ca 2+ (K a = 0.5 × 10 5 m −1 ). [28] Since the resultant 2D materials in Figure 4c 1 -c 3 were micrometer-sized (Figure 5a,b), we believed they were too large to be endocytosed from outside the cell. This conclusion was confirmed by flow cytometric analysis of cells incubated with 2D-CB [6] extracted from their "mother" cells.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, photoswitchable fluorophores are of particular interest for sensing + imaging fiber probes. Photoswitchable metal-ion-sensitive fluorophores have been integrated with fibers via two methods: (i) attached to the fiber end of traditional solid fibers or the core surface along the length of suspended core MOFs [ 50 ] or (ii) embedded in a coating on the core surface along the length of exposed core MOFs [ 38 ]. Both methods have potential to be used for coating an imaging fiber to achieve a re-usable sensing + imaging fiber probe.…”
Section: Future Directionsmentioning
confidence: 99%
“…Sylvia et al reported the rational design and photophysical characterization of spiropyran-based chemosensors for magnesium (Mg 2+ ), a divalent cation important in mammalian cell function [2]. The sensor showed up to a two-fold increase in fluorescence upon interaction with Mg 2+ and had a three-fold higher dissociation constant for Ca 2+ , as compared to the Kd value for Mg 2+ .…”
Section: The Special Issuementioning
confidence: 99%